The Role of BDNF/TrkB Signaling in Acute Amphetamine-Induced Locomotor Activity and Opioid Peptide Gene Expression in the Rat Dorsal Striatum - McGinty, Jacqueline F.; Bache, Alexandra J.; Coleman, Nortorious T.; Sun, Wei-Lun (Frontiers in Systems Neuroscience, 2011)
Exposure to psychostimulants increases brain-derived neurotrophic factor (BDNF) mRNA and protein levels in the cerebral cortex and subcortical structures. Because BDNF is co-localized with dopamine and glutamate in afferents to the striatum of rats, it may be co-released with those neurotransmitters upon stimulation. Further, there may be an interaction between the intracellular signaling cascades activated by dopamine, glutamate, and TrkB receptors in medium spiny striatal neurons. In the present study, the effect of acute amphetamine administration on TrkB phosphorylation (p-TrkB), as an indirect indicator of activation, and striatal gene expression, was evaluated. In Experiment 1, 15 minutes or 2 hours after a single saline or amphetamine (2.5 mg/kg, i.p.) injection, the caudate-putamen (CPu), nucleus accumbens (NAc), and dorsomedial prefrontal cortex (dmPFC) were extracted and processed for phospho (p)-TrkB immunoreactivity. Immunoprecipitation analyses indicated that neither the tyrosine phosphorylation (p-Tyr) or autophosphorylation sites of TrkB (706) were changed in NAc, CPu, or dmPFC 15 min after amphetamine administration. In contrast, p-Tyr and the PLCγ phosphorylation site of TrkB (816) were increased in the NAc and CPu 2 hrs after amphetamine. In Experiment 2, intra-striatal infusion of the tyrosine kinase inhibitor, K252a, increased amphetamine-induced vertical activity but not total distance traveled. In addition, K252a inhibited amphetamine -induced preprodynorphin, but not preproenkephalin, mRNA expression in the striatum. These data indicate that acute amphetamine administration induces p-TrkB activation and signaling in a time- and brain region-dependent manner and that TrkB/BDNF signaling plays an important role in amphetamine-induced behavior and striatal gene expression.